Black Skin, White Masks - Fanon, Frantz (UK; Penguin Random House UK, 2021)
Frantz Fanon's urgent, dynamic critique of the effects of racism on the psyche is a landmark study of the black experience in a white world. Drawing on his own life and his work as a psychoanalyst to explore how colonialism's subjects internalize its prejudices, eventually emulating the 'white masks' of their oppressors, it established Fanon as a revolutionary anti-colonialist thinker.
English
Keywords: 20th century; Colonised people; HN1-995 Social history and conditions. Social problems. Social reform; Racism